2014
DOI: 10.1530/eje-14-0150
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver largely explains associations of subclinical hypothyroidism with insulin resistance, metabolic syndrome, and subclinical coronary atherosclerosis

Abstract: Background: The association of subclinical hypothyroidism (SCH) with insulin resistance, metabolic syndrome (MS), and coronary atherosclerosis is uncertain. Objective: To investigate the role of increased intrahepatic fat in the association of SCH with insulin resistance, MS, and coronary atherosclerosis. Design, patients, and methods: We conducted a cross-sectional study in a sample of 753 subjects (46% males) aged 35-70 years with no history of diabetes, renal, hepatic, thyroid, or coronary heart disease, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 41 publications
3
36
0
2
Order By: Relevance
“…Posadas-Romero et al (24) found that patients with subclinical hypothyroidism have significantly higher triglyceride levels and decreased HDL-C. Similar results were observed by Siemiński et al (25), who found elevated serum concentrations of cholesterol and triglycerides, while HDL-C was lower in women with subclinical hypothyroidism compared to the euthyroid postmenopausal women.…”
Section: Discussionsupporting
confidence: 70%
“…Posadas-Romero et al (24) found that patients with subclinical hypothyroidism have significantly higher triglyceride levels and decreased HDL-C. Similar results were observed by Siemiński et al (25), who found elevated serum concentrations of cholesterol and triglycerides, while HDL-C was lower in women with subclinical hypothyroidism compared to the euthyroid postmenopausal women.…”
Section: Discussionsupporting
confidence: 70%
“…El grupo control se formó con voluntarios de la población abierta, sin manifestaciones clínicas de EAC y sin antecedentes familiares de EAC prematura, que acudieron por invitación a través de medios escritos. De ambos grupos se excluyeron los pacientes con enfermedad renal, hepática o tiroidea, con enfermedades malignas o bien que tuvieran tratamiento con corticosteroides 16 . El proyecto fue aprobado por el Comité de Ética del Instituto Nacional de Cardiología Ignacio Chávez y realizado de acuerdo con los lineamientos de la Declaración de Helsinki.…”
Section: Métodosunclassified
“…We decided to include in this work the measurement of following parameters in a selected group: glycated haemoglobin (HbA1c) [4][5][6][7], high-sensitivity C-reactive protein (hs-CRP) [8][9][10], thyrotropin (TSH) [11][12][13][14], microalbuminuria [15][16][17], especially for their good cost-efficiency and easy accessibility.…”
Section: Introductionmentioning
confidence: 99%